Contemporary Qur’anic Lithography in Indonesia: Aesthetic of Reception of the Marble Al-Qur’an Manuscript - Nurani, Shinta; Maulana, Luthfi (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2022)
This study discusses the marble manuscripts of the Al-Qur’an and the meaning of its aesthetic reception manuscripts. The type of research is field research with the research locus at Masjid Al-Muhtaram, Kajen, Pekalongan Regency as a place to store the marble stone manuscripts. This study used Wolfgang Iser’s reception theory. Therefore, the results of this study are (1) the marble stone Manuscript of the Qur’an made by Nur Hidayat Siba that started in 2011 until 2021. It has reached 13 juz of Qur’an derived from marble measuring 60 x 90 cm with a marble thickness of 2 cm. It is also written with beautiful khat and gold colour wrapping on every khat. (2) Those manuscript provides three meanings of aesthetic reception. First, the objective meaning of the Qur’an as a holy book must be preserved through beautiful media as a form of appreciation for the greatness of the Qur’an. Second, the expressive meaning is used as a medium of Islamic da’wah, and spirituality increases faith and religious aspects for those who see and read it. Third, the meaning of documentary as a form of habitus to always interact with the Qur’an in everyday life.